A Methods engineering study of Flora-Generic Ventures, Incorporated - Balde, Bernard Roy (College of Engineering, 1994)
Flora Generic Ventures Inc. was the site chosen by the group to conduct a work study. Flora-Generic Ventures Inc. is a company which specializes in the production of artificial flowers and decors. The group commenced by gathering the necessary data and information about the company. Plant visits were conducted to document the existing Production Processes and the Systems and Procedures of the company. The team, in turn, took photographs of the company's operations and miscellaneous activities. The first part of the study is concerned mainly on the production process of the company. The group was informed about the main problem of the company which is the difficulty encountered in meeting deadlines of their clients during peak periods. In analyzing the production process along with the gathered data, the group was able to pinpoint three possible causes of the problem : (1) bald layout; (2) bad working conditions; and (3) bad planning of production processes. The group also came up with proposals for the solution of the problem. Criteria along with their respective weights were furnished so that each alternative could be evaluated and the best solution could be arrived at. After assessing the worth of each alternative, the group was able to choose the best solution. The group's proposal was to hire more workers specifically in the Assembly section where the group has observed to be a "bottleneck" problem and is a major contributor to the main problem of the company. The team also recommended to alter the plant layout so as to make the necessary adjustments in implementing the proposed solution. The second part deals in the Analysis of the Systems and Procedures of the company. Although the group perceived that there was no problem in the administrative activities which would contribute to the major problem of the company, the team felt that altering the office layout and revising the Organizational setup would aid in the smoother flow of documents and papers.